ANALISIS PESAN DAKWAH PADA DEPOT NABIL DALAM MENYAMPAIKAN DAKWAH KE MASYARAKAT NAGARI PASIA, KECAMATAN AMPEK ANGKEK, KABUPATEN AGAM - Hisyam Hisyam; Desi Syafriani (Jurnal Komunikasi, 2024)
Nagari Pasia, situated in the Ampek Angkek Subdistrict of Agam Regency, is one of the regions within Agam Regency that is actively endeavoring to enforce Islamic principles in the form of enjoining what is right and forbidding what is wrong, commonly known as "amar ma'ruf nahi mungkar." Among the multitude of merchants in Nagari Pasia, Mr. Andri Kusuma stands out as a household goods vendor. Within Mr. Andri's establishment, he oflers a wide array of products ranging from essential commodities to a water refilling station, operating under the name "Depot Nabil." This enterprise was established in the year 2020, coinciding with the onset of the pandemic in Indonesia. Mr. Andri's motivation behind the establishment of Depot Nabil is twofold: to generate profits and to sustain the daily livelihood of his family. An intriguing aspect uncovered during the researcher's observation is that, alongside his commercial activities, Mr. Andri, operating under the banner "Depot Nabil," has prominently displayed numerous banners within his establishment. These banners adorn nearly the entire interior, bearing content centered around Islamic propagation or 'dakwah.' These banners are replete with exhortations, invitations, and calls to abstain from acts forbidden by Allah SWT, such as associating partners with Allah. They also advocate for acts of worship and virtuous deeds, including Sunnah fasting, Quranic recitation, and charitable giving. Furthermore, these banners provide guidance and prohibitions for the Muslim community and reference various Islamic propagation websites and recommended social media outlets